Morphological differences in the pancreas of normo- and hypertensive rats after joint exposure of intermittent hypoxia and melatonin - Yanko, Roman V.; Levashov, Mikhail I. (Experimental Biology and Biotechnology, 2021)
The morphological changes in the pancreas of normo- and hypertensive rats after combined exposure to intermittent normobaric hypoxia and melatonin were studied. The study was conducted in the autumn on 24 normotensive (Wistar line) and 24 spontaneously hypertensive (SHR line) male rats. Experimental rats were daily exposed to hypoxic gas mixture in special sealed chamber. Hypoxic gas mixture (12 % oxygen in nitrogen) was supplied into this chamber from the membrane gas separator element in the intermittent mode: 15 min deoxygenation/ 15 min reoxygenation for 2 h. Exogenous melatonin was orally administered to experimental animals at 10 h in the morning at a dose of 5 mg / kg once a day. The total duration of the experiment was 28 d. Histological preparations of pancreatic tissue were prepared according to the standard methods. The morphometry of the preparations digital images was performed using the computer program ImageJ. The nature and severity of morphological changes in the pancreas of the experimental spontaneously hypertensive rats (hyperplasia of the nucleolus in the nucleus of exocrinocytes, a decrease in the amount of connective tissue) suggests that the combined effect of intermittent normobaric hypoxia and melatonin increases the activity of the exocrine part of the pancreas. At the same time, the activity of the endocrine part of the pancreas decreases, as evidenced by a decrease in the linear dimensions and area of the Langerhans islets, as well as the number of endocrinocytes contained in them. In Wistar rats, the combined effect of intermittent hypoxia and melatonin leads to the appearance of morphological signs of increased activity of both exocrine and endocrine pancreas functions. Thus, after prolonged combined exposure to intermittent normobaric hypoxia and melatonin, morphological signs of increased exocrine pancreas activity appear in both normotensive and hypertensive rats. At the same time, the activity of the endocrine function of the pancreas in experimental Wistar rats increases, while in SHR rats, on the contrary, decreases.